ANTI-HYPERTENSIVE DRUGS USED DURING PREGNANCY - Saugat Dahal1Sushobhan Bhandari1* Sanju Kharel1Deepak Bhatt1 (Journal of Biomedical and Pharmaceutical Research, 2017)
Hypertension is a major cause of maternal and fetal mortality during pregnancy. Estimated to cause complications in around 15% pregnancies, hypertension is the most commonly encountered medical complication during pregnancy. The use of antihypertensive therapy during pregnancy is validated by weighing risks and benefits of the therapy. This review comprises of various antihypertensive drugs used as a treatment guideline for treating different types of hypertension during pregnancy. Severe hypertension during pregnancy poses enormous risk to both mother and fetus and should be treated immediately. Treatment can drastically decrease the risk and can result in an uncomplicated pregnancy. This review comprises the use of methyldopa, clonidine, β-adrenoceptor antagonists (labetalol), prazosin, vasodilators (hydralazine), calcium channel blockers (nifedipine, nicardipine), loop diuretic, thiazide diuretic, and its safety and efficacy for treating hypertension during pregnancy. Keywords: Hypertension in pregnancy, preeclampsia, antihypertensive drugs and fetus, teratogenicity, fetotoxicity.